RANCANG BANGUN APLIKASI PRESENSI KARYAWAN BERBASIS ANDROID DENGAN GLOBAL POSITIONING SYSTEM DI PT. GRAHAMAS INTITIRTA - Jaenal Gopur Asmanul Salam; Aris Hardiansyah (Jurnal Fakultas Teknik Kuningan, 2024)
Attendance is one of the important performance appraisals. The attendance made by each worker will affect the amount of salary earned each month by looking at how often workers come in late. PT. Grahamas Intitirta is one of the companies providing Air Minum Dalam Kemasan (AMDK). Currently the attendance system is carried out at PT. Grahamas Intitirta still uses a presence system using finger print and when going for leave, sick and overtime permission still uses a form that must be signed by superiors, so there are many deficiencies in terms of users (workers), admins and superiors (supervisors) to see and get data recapitulation attendance made. The purpose of this study was to design an Android-based application system to make it easier for users to take attendance and apply for absences from work due to leave, illness and applying for overtime. The development method used in designing android-based presence applications is the Waterfall Method. System design using the Unified Modeling Language (UML). System coding is done using Java, PHP and MYSQL. The results of this study are the Design and Build of Android-Based Presence Applications Using the Global Positioning System at PT. Grahamas Intitirta